SYSTEMATIC REVIEW: ZOONOSIS ASSOCIATED WITH MOUSE AND RAT - Agustina, Kadek Karang (Buletin Veteriner Udayana, 2024)
Mouse and rat borne zoonotic diseases refer to illnesses that can be transmitted from rodents such as mice and rats to humans. These animals can carry various pathogens, including bacteria, viruses, and parasites, which can cause diseases in humans through direct contact, inhalation of airborne particles, consumption of contaminated food or water, or via vectors such as ticks and fleas. Here are some common mouse and rat zoonotic diseases: Leptospirosis, Hantavirus Pulmonary Syndrome (HPS), Lymphocytic Choriomeningitis (LCM), Rat-Bite Fever (RBF), Salmonellosis dan Pes. Leptospirosis: This bacterial infection is caused by Leptospira bacteria found in the urine of infected rodents. Humans can contract leptospirosis through contact with contaminated water, soil, or food. Symptoms can range from mild flu-like illness to severe complications involving the kidneys, liver, and other organs. Hantavirus Pulmonary Syndrome (HPS): Hantaviruses are transmitted to humans through contact with rodent urine, droppings, or saliva, primarily from deer mice. Inhalation of aerosolized virus particles is the most common route of transmission. HPS can lead to severe respiratory illness, with symptoms including fever, muscle aches, coughing, and potentially fatal pulmonary edema. Lymphocytic Choriomeningitis (LCM): LCM is caused by the Lymphocytic Choriomeningitis Virus (LCMV), which is carried by house mice. Humans can become infected through exposure to rodent urine, droppings, saliva, or nesting materials. LCM can cause flu-like symptoms initially and may progress to more severe neurological complications, including meningitis and encephalitis. Rat-Bite Fever (RBF): This bacterial infection is caused by Streptobacillus moniliformis (commonly associated with rat bites) or Spirillum minus (associated with exposure to rat feces or urine). RBF can result from a bite or scratch from an infected rodent or handling of contaminated materials. Symptoms include fever, rash, joint pain, and in severe cases, endocarditis or meningitis. Salmonellosis: Salmonella bacteria can be carried by rodents, particularly in their feces. Humans can contract salmonellosis through the ingestion of contaminated food or water, as well as through direct contact with rodents or their habitats. Symptoms typically include diarrhea, abdominal cramps, fever, and vomiting. Pes: While commonly associated with fleas that infest rodents like rats, plague bacteria (Yersinia pestis) can also be transmitted directly through contact with infected rodents or their bodily fluids. Plague can manifest as bubonic (swollen lymph nodes), septicemic, or pneumonic forms, with symptoms ranging from fever and chills to respiratory distress and organ failure. Preventing mouse and rat zoonotic diseases involves maintaining good hygiene practices, such as proper food storage, waste disposal, and rodent-proofing buildings. Additionally, avoiding contact with wild rodents and seeking prompt medical attention if exposed to rodents or experiencing symptoms of illness are crucial preventive measures.